Association between visceral obesity and hepatitis C infection stratified by gender: a cross-sectional study in Taiwan. Issue 11 (12th November 2017) - Tsao, Yu-Chung; Chen, Jau-Yuan; Yeh, Wei-Chung; Peng, Yun-Shing; Li, Wen-Cheng
Abstract : Objectives: The global prevalence of hepatitis C virus (HCV) is approximately 2%–3%, and the prevalence of the positive anti-HCV antibody has been increasing. Several studies have evaluated regional adipose tissue distribution and metabolism over the past decades. However, no study has focused on the gender difference in visceral obesity among patients with HCV infection. Design: Retrospective cross-sectional study. Setting: We reviewed the medical records of patients who visited a hospital in Southern Taiwan for health check-up from 2013 to 2015. Participants: A total of 1267 medical records were collected. We compared patient characteristics, variables related to metabolic risk and body composition measured using bioelectrical impedance analysis between the groups. Regression models were built to adjust for possible confounding factors. Results: The prevalence rate of the positive anti-HCV antibody was 8.8% in the study population, 8.5% in men and 9.2% in women. Men with HCV infection tended to be older and have lower total cholesterol levels and higher alanine aminotransferase (ALT) levels (p<0.001). Women with HCV infection tended to be older and have higher levels of fasting glucose and ALT (p<0.001). After adjusting for confounding factors, body fat percentage, fat-free mass/body weight (BW) and muscle mass/BW were found to be the independent determinants of visceral obesity in patients without HCV infection (p<0.001). However, the trend was not such obvious in patients with HCV infection, though still statistically significant (p<0.05). Furthermore, the trend was less significant in men with HCV infection. Conclusions: The findings suggested that HCV modulates host lipid metabolism and distribution to some extent, and a gender difference was also noted.